Nutritional and metabolic assessment of HIV patients in use of antiretroviral therapy at Northeastern Brazil - doi: 10.5020/18061230.2010.p368 - Liana Aguiar Braga; Carlos Antonio Bruno da Silva (Universidade de Fortaleza, 2012)
Objective: To evaluate nutritional and metabolic changes in HIV infected (HIV+) patients on use of antiretroviral therapy. Methods:  A cross-sectional descriptive study involving HIV+ patients on use of Highly Active Antiretroviral Therapy (HAART). The demographic data studied were gender, birth date and time of use of antiretroviral medication. Anthropometric variables were weight and height with calculation of body mass index (BMI). Biochemical data were lipid profile, blood glucose, renal function, albumin, uric acid, oxalacetic and pyruvic transaminases and red blood cells count. Results: The study population comprised 70 patients, 36 (51.4%) men and 34 (48.6%) women with an average time of HAART-use of 34.5 + 16.5 months. We observed a prevalence of 42 (60%) healthy weight for BMI, changes in lipid profile and reduction of lean mass in 18 (50%) men and increased abdominal obesity in 23 (67.7%) women. Conclusion: The studied subjects in use of HAART showed to have loss of subcutaneous fat, lipid changes and higher prevalence of abdominal obesity in women.